The relationship between gender segregation in schools, self-esteem, spiritual values/religion, and peer relations in Kuwait - Lujain AlMatrouk (19811637) (2016)
Public schools at all levels in Kuwait are gender-segregated due to conservative traditional values, but such segregation is not practiced in private schools. In the past decade, a series of laws were passed to impose gender segregation in private universities as well. A concern about the psychological and social impact of gender segregation on students is a topic of ongoing debate in Kuwait. Research into the effects of gender segregation on social aspects such as peer relations remains an area to be explored. The purpose of this study is to assess whether there is a difference in peer relations with the opposite or same gender among individuals who have attended Kuwaiti schools across different school settings, and to explore which factors such as physical appearance, general esteem, parental relations, and spiritual values/religion might influence this difference. Seventy-six participants (57% female; 43% male) in Kuwait aged between 18 and 39 years filled out an online questionnaire incorporating scales related to the variables of interest taken from Marsh's Self-Description Questionnaire III. The results showed that participants who attended a mixed-gender school, as opposed to a segregated school, in Kuwait scored significantly higher on the peer relations with the opposite gender criteria, meaning that they believed they had good relationships with peers of the opposite gender (M = 44.1; P < 0.05). The results showed that school setting was a significant predictor of peer relations with the opposite gender (β = 0.251, P < 0.05); however, when additional factors such as self-esteem, parental relations, physical appearance, and spiritual values/religion were controlled for, schooling was not found to be a significant predictor of peer relations, and self-esteem had the highest significant relationship with peer relations of the same and opposite gender as well (β = 0.461, P < 0.01; β = 0.623, P < 0.001). Spiritual values/religion had a significant relationship with peer relations of the same gender only and not the opposite gender, meaning the more religious the individuals believed they were, the less they thought that they had good relationships with peers of the same gender (β = − 0.295, P < 0.01). Self-esteem scores were highly significantly correlated with parental relations scores and physical appearance scores (r = 0.605; r = 0.577; P < 0.01). The implications of the data on educational policy as well as the importance of spreading awareness about the significant relationship that self-esteem and spiritual values/religion can have with peer relations in Kuwait are discussed. Other Information Published in: Near and Middle Eastern Journal of Research in Education, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/nmejre.2016.3